ANALISIS PENERIMAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) BAGI PENYULUH DALAM KEGIATAN PENYULUHAN PERTANIAN - Arifin, Miftakhul (Jurnal Ilmu-Ilmu Pertanian, 2016)
This study is a survey research on Acceptance Analysis of Information and Communication Technology (ICT) for Extension Workers in Agricultural Extension Activities. The research objective was to determine the effect of variable Perceived Ease of Use of ICTs on Perceived Usefulness use of ICT, the influence of Perceived Ease of Use of ICTs on Intensity Behaviour Using ICT, influence perception Usefulness use of ICT to the intensity of Behaviour Using ICT, and the influence of Intensities Behaviour Using ICT to the use of ICT in Currents. This type of research is explanatory research by using the Technology Acceptance Model (TAM), and involve agricultural extension workers as respondents. Data were collected using questionnaires and then analysed by quantitative descriptive and hypothesis testing and regression analysis. The results of the study are (1) the results of descriptive analysis of the four variables are variables Perceived Ease of Use of ICT, variable Perceived Usefulness use of ICT, variable intensity Behaviour use of ICT, and variable use of ICT In Currents has an average category High, (2) Test Results Hypothesis analysis simple linear regression, namely: (a) for the variable Perceived Ease of Use ICTs to variable Perceived Usefulness use of ICT, and variable Perceived Ease of Use ICTs to variable intensity of the use of ICT has a significant influence (b) While the variable Perceived Usefulness Using ICT to variable intensity Behaviour of Use ICT, and the variable intensity of Behaviour Using ICT to variable use of ICT in Currents not significant. The implication of this research is very necessary in their outreach activities using ICTs to improve the success of the field of education, and what is important is the use of ICT must be effective and efficient.